2013
DOI: 10.1016/j.chroma.2013.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Improved separation and detection of picolinic acid and quinolinic acid by capillary electrophoresis-mass spectrometry: Application to analysis of human cerebrospinal fluid

Abstract: “Quinolinic acid (QA)”, a metabolite of the kynurenine pathway (KP), is implicated as a major neurological biomarker, which causes inflammatory disorders, whereas there is an increase evidence of the role of picolinic acid (PA) in neuroinflammation. Therefore, there is an urgent need to develop new clinical test for early diagnosis of neuroinflammatory disorders. A comparison is made between three different platforms such as high performance liquid chromatography–electrospray mass spectrometry (HPLC–ESI-MS/MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It has not yet been established whether PIC is able to cross the BBB and enter CNS from the periphery under physiological conditions, but PIC is readily detectable in CSF samples from humans (own unpublished observations) (Coggan et al, 2009; Wang et al, 2013). ACMSD is expressed in the brain, although the expression rate is lower than in kidney and liver (Pucci et al, 2007).…”
Section: Kynurenine Pathway Metabolites In Psychiatric Disorders Amentioning
confidence: 99%
“…It has not yet been established whether PIC is able to cross the BBB and enter CNS from the periphery under physiological conditions, but PIC is readily detectable in CSF samples from humans (own unpublished observations) (Coggan et al, 2009; Wang et al, 2013). ACMSD is expressed in the brain, although the expression rate is lower than in kidney and liver (Pucci et al, 2007).…”
Section: Kynurenine Pathway Metabolites In Psychiatric Disorders Amentioning
confidence: 99%
“…They identified choline, dimethylarginine, arginine, valine, proline, serine, histidine, creatine, carnitine, and suberylglycine as possible disease progression biomarkers. The comparison of various platforms of LC‐ESI‐MS/MS with CE‐ESI‐MS/MS revealed that using a quaternary ammonium‐coated capillary, CE combination is the best method for analysis of quinolinic acid, a metabolite of the kynurenine pathway, and picolinic acid involved in neuroinflammation . Consequently, the method was successfully applied to analyze both acids in cerebrospinal fluid demonstrating the potential of this method to accurately quantitate with high specificity and sensitivity.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Wang et al. published a method for sensitive determination of the neurological biomarkers quinolinic and picolinic acid in cerebrospinal fluid by CE‐ESI‐MS/MS. They used a (vinylbenzyl)trimethylammonium‐coated capillary and 15 mM (NH 4 ) 2 CO 3 at pH 11.0 as the BGE.…”
Section: Combined Stacking Techniquesmentioning
confidence: 99%